Synthesis of 2-cyanoacrylamides through Pd-catalyzed monohydration of methylenemalononitriles. Issue 5 (4th March 2019) - Liu, Yingtian; Dang, Xinxin; He, Yu; Bai, Hudong; Chen, Xuehong; Li, Jun-Long; Fan, Junting; Jiang, Hezhong; Li, Jiahong
Abstract: A straightforward and efficient method has been developed for the synthesis of 2-cyanoacrylamide from 2-methylenemalononitriles through monohydration. A series of methylenemalononitriles underwent the reaction under mild and simple reaction conditions with good to excellent yield. Graphical Abstract: